Antioxidant and antimicrobial activity of ultra-filtered fractions of camel milk protein hydrolysates under in-vitro condition - KUMAR, DEVENDRA; CHATLI, MANISH KUMAR; SINGH, RAGHVENDAR; MEHTA, NITIN; KUMAR, PAVAN (The Indian Journal of Animal Sciences, 2017)
Sequential ultra-filtration technique was used to fractionate camel milk protein hydrolysates products by 3 different proteolytic enzymes, viz. alcalase, α-chymotrypsin and papain. The protein fractions were assessed for antioxidant activities, viz. 2,2-azino-bis(3-ethylbenzthiazoline-6-sulphonic acid) (ABTS), 2,2-diphenyl-1 picrylhydrazyl (DPPH) and ferric reducing antioxidant power assay (FRAP), and antimicrobial activity (inhibition zone assay). The whole hydrolysates recorded significantly higher inhibition activity in ABTS, DPPH and FRAP assay, whereas among fractions, F2 (1-5 kDa) and F3 (5-10 kDa) of all the 3 hydrolysates had higher activity. Higher antioxidant activities was also observed in α- chymotrypsin hydrolysates samples and its fractions followed by alcalase and papain. The zone of inhibition (mm) was also recorded higher for whole hydrolysates as compared to their fractions; however, different fractions had almost comparable antimicrobial effect. The protein hydrolyastes with alcalase and α- chymotrypsin recorded comperatively higher antimicrobial activity. The findings suggested that camel milk proteins could be valuable source to produce protein hydrolysates and ultra-filtration technique could also be used to get specific molecular weight peptides, however, for application in processed food or for direct human consumption, use of whole hydrolysates could be more beneficial and cost effective.